Assessment of C-Reactive Protein Concentrations in Patients with COVID-19: A Laboratory-Based Observational Research Study - Abdalla Hamed; Fati Alshourif; Mohamed Elwafi (AlQalam Journal of Medical and Applied Sciences, 2026)
COVID-19 represents a significant health crisis due to its high transmissibility and elevated mortality rates among critically ill patients. The understanding of the pathological and physiological mechanisms, as well as the diagnostic approaches for COVID-19, remains in the early stages of investigation. Effective clinical monitoring and suitable treatment strategies are crucial for reducing mortality rates. This study aimed to measure the levels of C-reactive protein (CRP) and ferritin in patients diagnosed with COVID-19. A retrospective study was carried out in the Yafran Pathology Center and Analysis Laboratory, Andalusia District, where blood samples from confirmed COVID-19 positive patients were processed following standard laboratory protocols. CRP and ferritin levels were assessed using the Integra 400Plus system. The study involved 117 patients, including both males and females, and they were categorized according to age into groups. 0-17 years, 18-34 years, 35-49 years, 50-64 years, 65 years and older. In conclusion, elevated CRP levels are associated with a more severe disease trajectory, linked to lung damage and poorer prognosis.